Między demokratyzmem a autorytaryzmem — kształtowanie się programu politycznego PPS przed i po maju 1926 roku - Kowalski, Wawrzyniec (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article presents the political debate which took place within the Polish Socialist Party after 1905, regarding the selection of real means to achieve its political goals. The Polish Socialist Party in the period of the Second Polish Republic was an evolutionist and democratic organization, standing in opposition to the ideas of an authoritarian state. The party leaders dissented from achieving political program objectives through methods typical of revolutionary radicalism. The authoritarian fascinations of the May 1926 coup d’etat in the long-term did not lead to a re-evaluation of the political program adopted at the moment of independence.
Keywords: polski autorytaryzm w II Rzeczypospolitej Polskiej; demokracja; program polityczny Polskiej Partii Socjalistycznej; maj 1926 r. zamach stanu; parlamentaryzm w II Rzeczypospolitej Polskiej; bezpieczeństwo